IDeaLs (innovation and design as leadership) - Press, Joseph; Bellis, Paola; Buganza, Tommaso; Magnanini, Silvia; Trabucchi, Daniel; Shani, Abraham B. (Rami); Verganti, Roberto; Zasa, Federico Paolo (Emerald Publishing Limited, 2021)
As society faces significant disruptions, the need for transformative innovation has never been more vital. However, this urgency is challenged in the digital era, characterized by incessant new technologies, extreme connectivity, and data transparency. Leaders seeking transformative innovation in the digital era face a new dilemma: socially orchestrating the synchronization of ideas that simultaneously encourages collective action. IDeaLs - Innovation and Design as Leadership - was established to research this conundrum. Inspired by the actual transformation journeys of multinational companies, and based on research with 7 global companies, IDeaLs explores how re-framing our traditional theories through the lens of Humanism reveals opportunities for a more integrated approach to engaging people for systemic change. To empower innovation leaders, the dimensions of IDeaLs build a scaffold for systemic awareness and conscious intent called Design-Driven Transformation. This evolving research agenda aims to examine in-depth the potency of an integrated approach, laying a foundation for more systemic ways to engage people and transform existing situations into preferred futures.